PS01.031: REVISITING THE ESOPHAGOGASTRIC JUNCTION ANATOMY: WHERE IS THE INFRACARDIAC BURSA?. (14th September 2018) - Nakamura, Tatsuro; Shinohara, Hisashi; Okada, Tomoaki; Hisamori, Shigeo; Tsunoda, Shigeru; Obama, Kazutaka; Kurahashi, Yasunori; Takai, Akihiro; Takakuwa, Tetsuya; Yamada, Shigehito; Sakai, Yoshiharu
Abstract: Background: The infracardiac bursa (ICB), the closed space encountered in the esophagogastric junction (EGJ) surgery, is rarely described in anatomical atlases. The purpose of the study is to link surgery to embryology and propose the new anatomical chart including the ICB. Methods: Histological serial sections of Carnegie stages (CS) 13–23 embryos and magnetic resonance (MR) images of the fetus with 43.5 mm crown-rump length from the Kyoto Collection of Human Embryos were examined for embryological changes in the ICB. Seventy-four surgery videos of laparoscopic and thoracoscopic esophagectomy were reviewed to investigate the appearance of the ICB and frequency of the recognition in surgery. Results: The right pneumato-enteric recess appeared in CS13 embryos and the ICB was separated from the recess by the development of the diaphragm between CS17 and CS18 embryos and established as a closed space up until CS23. The three-dimensional reconstruction of fetus MR images showed the ICB was located adjacent nearly one third around the esophagus above the right crus. The ICB was clinically encountered in 12 of 14 (86%) transhiatal surgeries and 23 of 60 (38%) thoracic surgeries. Via the transhiatal approach, the caudal edge of the ICB appeared as a thick whitish membrane after the dissection of the phrenico-esophageal ligament and a closed space enveloped with a serosa was opened by the incision of the membrane. Via the right thoracic approach, the ICB appeared on the right crus after the dissection of the pulmonary ligament. Conclusion: We described a new chart around EGJ including the ICB based on embryology. This anatomical chart can contribute to promote accuracy and safety of operating procedures around the EGJ. Disclosure: All authors have declared no conflicts of interest.